2008
DOI: 10.1063/1.2904458
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension of water and acid gases from Monte Carlo simulations

Abstract: We report direct Monte Carlo (MC) simulations on the liquid-vapor interfaces of pure water, carbon dioxide, and hydrogen sulfide. In the case of water, the recent TIP4P/2005 potential model used with the MC method is shown to reproduce the experimental surface tension and to accurately describe the coexistence curves. The agreement with experiments is also excellent for CO(2) and H(2)S with standard nonpolarizable models. The surface tensions are calculated by using the mechanical and the thermodynamic definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 47 publications
(101 reference statements)
4
107
0
Order By: Relevance
“…19, the equilibrated system (state 0) with interfacial area According to our results, we found that γ is constant in the range 10 -5 < ξ < 10 -3 . The value of ξ used in this work is 5 × 10 -4 , which is commensurate with previous other similar application of the TA method [68,[71][72][73][74][75] . All the TA calculations are performed by post-processing an uninterrupted MD run, as the perturbations have no effect on the dynamics of the system.…”
Section: Interfacial Tension Via the Ta Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…19, the equilibrated system (state 0) with interfacial area According to our results, we found that γ is constant in the range 10 -5 < ξ < 10 -3 . The value of ξ used in this work is 5 × 10 -4 , which is commensurate with previous other similar application of the TA method [68,[71][72][73][74][75] . All the TA calculations are performed by post-processing an uninterrupted MD run, as the perturbations have no effect on the dynamics of the system.…”
Section: Interfacial Tension Via the Ta Methodssupporting
confidence: 63%
“…This method, referred to as the test area (TA) method (see Gloor et al [68] Errington and Kofke [69] and Ghoufi et al [70] for a review of this approach) is used herein.…”
Section: Interfacial Tension Via the Ta Methodsmentioning
confidence: 99%
“…The computational procedures of the molecular simulation of the liquid-vapour interface can be found in previous papers [12,13,14,15,16,17]. The force-field used in the molecular modelling of the grafted system and the description of the computational procedures can be also found elsewhere [11].…”
Section: This Contribution Is the Correction Term From Yeh Andmentioning
confidence: 99%
“…We refer to this as the volume perturbation method (sometimes referred to as the ghost volume change method) [23][24][25][26][27][28][29] of pressure calculation. For a homogeneous phase the pressure can be obtained by [23][24][25][26][27][29][30][31][32] …”
Section: Volume Perturbation Methodsmentioning
confidence: 99%